Occurrence rates of wild rodent hosts and chigger mites and the infection rate of Orientia tsutsugamushi in the central region of South Korea from 2015 to 2018. Issue 8 (13th August 2019) - Choi, Moon Bo; Kim, Yeongbu; Kim, Da Young; Kwon, Ohseok
Abstract: Outbreaks of vector‐borne diseases are dramatically increasing because of climate change, consequently increasing the importance of surveillance of endemic disease vectors. In this study, we surveyed chigger mites, vectors for Orientia tsutsugamushi —the bacteria that causes Tsutsugamushi disease—, and their rodent hosts in Gimcheon, central South Korea, in 2015–2018. A total of 225 rodents were collected, with trap rate and percentage of rodents infected by chigger mites of 9.8 and 72.4%, respectively. Six species of rodents from five genera were collected, the most common rodent being Apodemus agrarius (n = 153, infection rate = 90.8%). The highest number of rodents was collected in spring (trap rate = 10.3), but the rate of infected rodents was higher in fall (81.5%) than in spring (61.3%). Trap rate was highest for bank near waterway (17.9), but the chigger index (CI) was highest in hill (224.1). A total of 20, 534 (CI 126.0) chigger mite individuals from 10 species and three genera were found on the collected rodents. The most common species was Leptotrombidium pallidum (n = 7, 982, 83.6%, CI 49.0), followed by L. palpale and L. scutellare . Chigger mites were most frequent at banks near waterway (n = 11, 093, CI 152.0) and hill (n = 2, 017, CI 224.1). To detect O. tsutsugamushi in chigger mites, 450 pools of chigger mites (n = 10, 991) were analyzed; 24 pools were positive—23 of A. agrarius, the most frequently collected species in South Korea, 1 of Micromys minutus —and the minimum positive rate (MPR) was 0.22. The detected strain types included Boryong (dominant in all years, seasons, and habitats), Jecheon, 07–489, and IIOC1202.